Draft Annual Plan 1980-81 Chandigarh Administration Planning and Statistical Cell - Planning Commission (Planning Commission, 1929)
Union Territory, Chandigarh came into existence in 1. 11.1966, with a-total area of 28, 249 acres, out of which 7,933 acres are cultivable at present. Community Block was, however, set up during the year 967-68 for the employment of the, villages, situated around Chandigarh. Since then note-worthy changes in the 'agricultural field took place as under Policy of disbursing loans for the purchase of tractors has been liberalized to the Administration. Ceiling for eligibility far tractor loan has been reduced from 20 acres to 1 0 acres so that maximum number of farmers could get the benefit under this scheme. These efforts have led to apt increase in-the number of tractors in Union Territory. Today, there are 69 tractors, against 3 in 1966
Chandigarh Administration Planning and Statistical Cell
Chandigarh Administration Planning and Statistical Cell (Finance Department)
Keywords: Central Polytechnic; Punjab Engineering College; College of Architecture; Public Health & Sanitation; Augmentation of Water Supply; Chandigarh Capital Project; Information and Publicity; Welfare of Scheduled; Castes and Backward Classes; Other General Economic; Improved Agricultural Implements; Small and Marginal farmers arid Agricultural laborers; Loans to Farmers for private Tube well.